Giving Reasons as Politeness Strategy in Refusal Speech Act: A contrastive analysis on Japanese native speakers and Indonesian Japanese learners refusal speech act - Nurjaleka, Lisda (JAPANEDU: Jurnal Pendidikan dan Pengajaran Bahasa Jepang, 2019)
Japanese Language considered as an HC (high context) language. It means that the context of communication is essential in socio-cultural discourses regarding Japanese language use. Nishijima (2007) stated that communicative behaviors are different in every language because of its’socio-cultural background. Japanese is a language that often considers other people’s feeling, especially interlocutor’s. This paper aims to analyze and explain how Japanese native speaker and Indonesian Japanese learners giving an explanation or reason ina refusal situation. The data in this study collected through DiscourseCompletion Test (DCT), consisting a single role-play situation which participant will read to elicit the response from another participant. The participants in this study including 16 Japanese Native Speakers (JNS) and 20 Indonesian Japanese Learners (IJL). The results of this study suggested that both JNS and IJL tend to explain their reason in a refusal situation based on the socio-cultural background in their language. JNS tend to make an excuse for the things that they can not do and ask if it may make their interlocutor in trouble because of their incapability. On the other hand, Indonesian tend to make an excuse because they feel they are incapable of doing the request.